The Use of Audio Qur’an Media via Smart Boards to Improve the Fluency of Memorization Among Fourth-Grade Students at SDIT Ibnu Rajab, Turikale Subdistrict, Maros Regency - Sumarni; Muhammad Warif; Mumtahanah; Muh. Ilham; Nurul Auliah (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
This study aims to determine the use of Qur’an audio media through Smart Board in the tahfidz learning process, its effectiveness in improving students’ memorization fluency, as well as obstacles and challenges in its implementation. The selection of SDIT Ibnu Rajab, Turikale District, Maros Regency is based on the use of Qur’an audio media through Smart Board in improving students’ memorization fluency. In addition to having a superior Qur’an tahfidz program, this school has also integrated learning technology to support improving the quality of memorization, accuracy of makhraj, and tajwid of students. This research is a qualitative research with a field research design using a case study approach. The data sources in this study consist of two types. First, primary data which is the result of interviews with the principal, tahfidz teachers and fourth grade students of SDIT Ibnu Rajab who are directly involved in tahfidz learning using Smart Board. Second, secondary data in this study were obtained from various relevant sources such as books, journals, and previous research related to Qur’an audio media, smart boards, and Qur’an memorization fluency. In qualitative research, the researcher acts as the primary instrument, planning, collecting, analyzing, and reporting the research results directly in the field through interactions with informants. Data collection techniques include observation, interviews, and documentation. Data analysis involves data collection, data reduction, data presentation, and conclusion drawing. Data validity is tested through source triangulation, technical triangulation, and time triangulation. The results of the study indicate that: (1) the use of audio Quran media via Smart Boards can increase student motivation, attention, and engagement in memorization; (2) audio Quran media via Smart Boards is effective in improving student memorization fluency because it helps students listen to and imitate Quran recitations more accurately, thus improving accuracy in pronunciation, tajweed, and memorization fluency; and (3) obstacles identified include limited learning time, suboptimal utilization of Smart Board features, and the need for consistent teacher support to ensure effective and sustainable use of the media.